Exploring TAS2R46 biomechanics through molecular dynamics and network analysis - Cannariato, Marco; Fanunza, Riccardo; Zizzi, Eric A.; Miceli, Marcello; Di Benedetto, Giacomo; Deriu, Marco A.; Pallante, Lorenzo (Frontiers in Molecular Biosciences, 2024)
Understanding the intricate interplay between structural features and signal-processing events is crucial for unravelling the mechanisms of biomolecular systems. G protein-coupled receptors (GPCRs), a pervasive protein family in humans, serve a wide spectrum of vital functions. TAS2Rs, a subfamily of GPCRs, play a primary role in recognizing bitter molecules and triggering events leading to the perception of bitterness, a crucial defence mechanism against spoiled or poisonous food. Beyond taste, TAS2Rs function is associated with many diseases as they are expressed in several extra-oral tissues. Given that the precise functioning mechanisms of TAS2R remain poorly understood, this study employed molecular dynamics simulations combined with network-based analysis to investigate local conformational changes and global structural correlations in different states of the receptor. The focus was on the human TAS2R46 bitter taste receptor, recently resolved experimentally, both in the presence and absence of strychnine, a known bitter agonist. The results showed that the ligand-bound state of the receptor exhibited more correlated dynamics compared to the apo state, and the presence of the agonist mediated the allosteric network between two helices (TM3 and TM6) which mainly convey the signal transferring from the extracellular to the intracellular region. By elucidating the hallmarks of the conformational changes and allosteric network of TAS2R46 under varying conditions, this study has enabled the identification of the unique structural and dynamics features of this receptor, thereby establishing a foundation for a more profound characterisation of this intriguing class of receptors.